Analysis of Micro, Small, And Medium Enterprises (MSMEs) Development Strategies With An Islamic Business Approach Ethics in Increasing Business Income - Siregar, Nurhasanah; Muhammad Yafiz; Nasution, Juliana (MALIA: Jurnal Ekonomi Islam, 2025)
Introduction: This study investigates the development strategy of Micro, Small, and Medium Enterprises (MSMEs) at RnD Snack Labuhanbatu Selatan through the perspective of Islamic business ethics. The research aims to explore how Islamic ethical values are integrated into business development to support sustainability and competitiveness. Methods: This research employs a qualitative descriptive approach by conducting in-depth interviews with business owners, employees, and three customers, as well as direct observation of operational activities. The data were analyzed using a combination of business strategy theory, Islamic business ethics principles, and the SWOT analysis framework. Results: The findings indicate that RnD Snack implements business strategies such as improving product quality, innovating menu options, enhancing customer service, promoting through social media, expanding market reach, and applying the Islamic marketing mix. All these strategies are aligned with Islamic ethical principles, including honesty, transparency, fairness, and generosity. Conclusion and suggestion: This study concludes that integrating Islamic business ethics into MSME development strategies contributes positively to sustainability and long-term performance. It is suggested that other similar businesses adopt ethical practices based on Islamic teachings to build customer trust and improve competitiveness.